Role of Damage-Associated Molecular Patterns in Septic Acute Kidney Injury, From Injury to Recovery - Ludes, Pierre-Olivier; de Roquetaillade, Charles; Chousterman, Benjamin Glenn; Pottecher, Julien; Mebazaa, Alexandre (Frontiers in Immunology, 2021)
Damage-associated molecular patterns (DAMPs) are a group of immunostimulatory molecules, which take part in inflammatory response after tissue injury. Kidney-specific DAMPs include Tamm-Horsfall glycoprotein, crystals and uromodulin, released by tubular damage for example. Non-kidney-specific DAMPs include intracellular particles such as nucleus (histones, high-mobility group box 1 protein [HMGB1]) and cytosol parts. DAMPs trigger innate immunity by activating the NRLP3 inflammasome, G-protein coupled class receptors or the Toll-like receptor. Tubular necrosis leads to acute kidney injury (AKI) in either septic, ischemic or toxic conditions. Tubular necrosis releases DAMPs such as histones and HMGB1 and increases vascular permeability, which perpetuates shock and hypoperfusion via Toll Like Receptors. In acute tubular necrosis, intracellular abundance of NADPH may explain a chain reaction where necrosis spreads from cell to cell. The nature AKI in intensive care units does not have preclinical models that meet a variation of blood perfusion or a variation of glomerular filtration within hours before catecholamine infusion. However the dampening of several DAMPs in AKI could provide organ protection. Research should be focused on the numerous pathophysiological pathways to identify the relative contribution to renal dysfunction. The therapeutic perspectives could be strategies to suppress side effect of DAMPs and to promote renal function regeneration.